Advances in the diagnosis of periprosthetic joint infection. (May 2013) - Cooper, H John; Della Valle, Craig J
<x xml:space="preserve">Abstract</x> Introduction: Identification of periprosthetic joint infection (PJI) is critical, as the treatment between infected and non-infected arthroplasties is fundamentally different and missing the diagnosis may lead to a delay in diagnosis and the potential for a decreased rate of treatment success. Yet in the absence of a true gold standard, the diagnosis of PJI can be elusive. Given the rising incidence of this PJI and the growing infection burden anticipated in coming years, much effort is being put toward improving diagnostic tests for PJI. Areas covered: The best current practice for diagnosis of PJI is to follow an algorithmic approach. Emerging technology such as advanced imaging modalities, increasing availability of serum markers, synovial fluid biomarker analysis and new point-of-care modalities offer the potential to greatly enhance our ability to identify PJI in the future. Expert opinion: As there has been more focus on the diagnosis of PJI in recent years, new tests have been developed. These new tests will need to be rigorously evaluated before being incorporated into the diagnostic algorithm. Synovial fluid biomarker analysis and greater access to point-of-care testing may allow the biggest improvements in the diagnosis of PJI in the near future.